The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2096531120931106
|View full text |Cite
|
Sign up to set email alerts
|

An Intersection of Mathematics Educational Values and Cultural Values: Pāsifika Students’ Understanding and Explanation of Their Mathematics Educational Values

Abstract: Purpose: This article investigates the mathematics educational values of Pāsifika students in New Zealand. It draws on student voice to examine Pāsifika students’ understanding of mathematics educational values and their reasons for rating values at different levels of importance. Design/Approach/Methods: The study involved Years 7 and 8 Pāsifika students from two low-socioeconomic middle schools. Students selected their most and least important mathematics educational value statements on a survey. Semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The focus is on mathematics educational values (Bishop, 1988(Bishop, , 1996 and their reasons, involving Pāsifika students in New Zealand. As in the research conducted by Dede et al (2021), Hunter (2021 acknowledges the values as being anchored in society, mathematics and mathematics education. Thus, the cultural background of the learner has a bearing on their values (Lee & Seah, 2015;Seah, 2016;Zhang, 2019;Zhang et al, 2016).…”
Section: Ecnu Review Of Education 4(2)mentioning
confidence: 99%
See 2 more Smart Citations
“…The focus is on mathematics educational values (Bishop, 1988(Bishop, , 1996 and their reasons, involving Pāsifika students in New Zealand. As in the research conducted by Dede et al (2021), Hunter (2021 acknowledges the values as being anchored in society, mathematics and mathematics education. Thus, the cultural background of the learner has a bearing on their values (Lee & Seah, 2015;Seah, 2016;Zhang, 2019;Zhang et al, 2016).…”
Section: Ecnu Review Of Education 4(2)mentioning
confidence: 99%
“…In her case, the scope of the research allows her to combine qualitative and quantitative approaches to identify what is important in mathematical education for the group of students, and to develop her own research survey rather than using results from existing ones, even taking the latter as the basis for the first. Hunter's (2021) research decisions are responses to the challenge of achieving equity in education, incorporating Pāsifika students' values to the existing educational discourses. Tang et al (2021) present results from a quantitative study on students' mathematics values in Chinese mainland.…”
Section: Ecnu Review Of Education 4(2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings of the study, the researchers argued how Korean students' values about mathematics and mathematics learning might explain their excellent performance despite a "negative" affective mode, as evidenced in large international comparative studies such as the Trends in International Mathematics and Science Study (TIMSS) and the Programme for International Student Assessment (PISA). Hunter's (2021) article reports a study that examined 134 Pāsifika students' beliefs of mathematics educational values and their reasons for rating values at different levels of importance.…”
Section: Fanmentioning
confidence: 99%
“…Clearly, both sets of values are underpinned by those of a collectivism society's and strongly focused on the wellbeing of the collective as a whole. In our recent research, we showed that students named family, respect, and collectivism as particularly important educational values they drew on as they engaged in mathematics in classrooms (Anthony, 2013;Hill et al, 2019;Hunter, 2021).…”
Section: Culturally Sustaining Mathematics Pedagogymentioning
confidence: 99%